Association of Some NKG2 gene Family and it’ s Polymorphism with Pulmonary Tuberculosis - Nktel Faaz AL-Saad 1 Mohammed A.K Alsaadi 2 Ali Hmood Al-saadi 3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The case-control study was aimed to evaluate the effect of NKG2D and NKG2F, gene polymorphism onsusceptibility to pulmonary tuberculosis in Babylon province.The polymorphism of NKG2D gene at (rs1049174) and (rs2255336) were detected for 60 PTBcases and 60 of control. For rs1049174, allele frequency for patients and control were significant(P<0.05) and the C allele represent the risk allele for PTB patients with odd ratio (95% CI) of 2.04(1.16-3.57) while G allele represent protective allele for control group with odd ratio (95% CI) of 0.49 (0.28-0.86), (P<0.05). The genotype (C/C, G/C, G/G) were (61.7, 30, 8.3)% respectively for PTB patients and(36.7, 50, 13.3)% respectively for control with significant association with disease (P<0.05). On the otherhand, the SSCP and sequencing results of rs2255336 revealed that there were no gene variation in rs2255336among patients and control subjects.The polymorphism of NKG2F gene at (rs1841958) was also detected for 60 PTB cases and 60 of control.For rs1841958, allele frequency between patients and control were insignificant (P>0.05). The genotypes(C/C, A/C, A/A) were (38.3, 40, 21.7)% respectively for PTB patients and (36.7, 40, 23.3)% respectively forcontrol with insignificant association between these genotype and PTB (P>0.05).